HUBUNGAN CORE SELF EVALUATION DENGAN DIMENSI SPIRITUALITAS KEPEMIMPINAN - Endang Sri Wahyuningsih; Hening Riyadiningsih; Sri Sundari (Majalah Imiah Manajemen & Bisnis, 2020)
Review on effective leadership both theoretically and empirically has been done, ranging from aspects of cognitive, affective, and conative. But studies that explore aspects of leadership spirituality are rarely. This study aims to explore spirituality dimension of leadership and how the relationship between dimensions of spirituality with personality traits, such as core self evaluation. The study had used quantitative approach. The results of correlation analysis of data collected from SMEs in Banyumas, indicate that is positive relationship between core self-evaluation with leadership spirituality. It proved that the core self-evaluations can be a predictor of spirituality dimension of leadership. Leaders who have spiritual values appeared positive aspects of the motivational and behavioral, which is expected to spread in the work environment so that it can create a positive organizational climate.